NEEDS ANALYSIS OF USING E-LKPD BASED ON LIVEWORKSHEET NATURAL SCIENCE LESSONS IN CLASS V ELEMENTARY SCHOOL - Siti Fatima; Adeng Slamet; Sri Sumarni (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2023)
One of the learning adaptation processes in the revolutionary era 4.0 is digital and interactive based student worksheets (LKPD). LKPDs that are more innovative and can be packaged in online form or can be called Electronic Student Worksheets (E-LKPD). This study aims to conduct a needs analysis of E-LKPD based on liveworksheets in science subjects in class V SD. This research was conducted at SDN 87 Palembang. Collecting data in this study using a questionnaire with qualitative data types. The data analysis technique used is descriptive analysis with data reduction, data presentation, conclusion and verification. The data that needs to be analyzed regarding the use of the types of teaching materials used, the implementation of learning, the evaluation system, and the factors that support it. The results of the needs analysis research showed that 46.9% answered that the learning method that was often used was discussion or question and answer and 84.4% of students answered that they had difficulty understanding science subjects in class. A total of 78.1% of students stated that they really needed liveworksheet-based E-LKPD teaching materials in the learning process in class. And 75% of students strongly agree if the use of the E-LKPD is equipped with interesting pictures, videos, audio and questions. It was concluded that E-LKPD based on Liveworksheets can be used as an alternative electronic teaching material.